Kajian Etimologi dan Terminologi Metodologi Pembelajaran Pendidikan Agama Islam - Darmiah Darmiah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Islamic religious education as a system is an activity that includes objectives, curriculum, teachers, methods, approaches, infrastructure, environment, management and others that are interrelated and form a unified system. The student education methodology must be adapted to the needs and characteristics of students, so that teachers can easily convey it to students, and students can also easily accept and understand lessons from teachers, because teachers can adjust to students' souls. . students with such learning. Methodology comes from the Greek language and consists of two words, namely